2017
DOI: 10.1302/2046-3758.62.2000619
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal and antimicrobial effects of pure titanium and titanium alloy treated with short-term, low-energy UV irradiation

Abstract: ObjectivesThe surface of pure titanium (Ti) shows decreased histocompatibility over time; this phenomenon is known as biological ageing. UV irradiation enables the reversal of biological ageing through photofunctionalisation, a physicochemical alteration of the titanium surface. Ti implants are sterilised by UV irradiation in dental surgery. However, orthopaedic biomaterials are usually composed of the alloy Ti6Al4V, for which the antibacterial effects of UV irradiation are unconfirmed. Here we evaluated the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Many of the metals, including gold or silver, have been used so far for the preparation of NPs, and demonstrate relatively strong antibacterial properties. Titanium compounds, especially titanium dioxide, were also used as a bactericide, as evidenced by numerous in vitro studies on various bacteria including both Gram-positive and Gram-negative strains [56,[73][74][75]. The antibacterial properties of titanium dioxide can be enhanced by exposure to UV light.…”
Section: Tio 2 Nanoparticles Combined With Phthalocyaninesmentioning
confidence: 99%
“…Many of the metals, including gold or silver, have been used so far for the preparation of NPs, and demonstrate relatively strong antibacterial properties. Titanium compounds, especially titanium dioxide, were also used as a bactericide, as evidenced by numerous in vitro studies on various bacteria including both Gram-positive and Gram-negative strains [56,[73][74][75]. The antibacterial properties of titanium dioxide can be enhanced by exposure to UV light.…”
Section: Tio 2 Nanoparticles Combined With Phthalocyaninesmentioning
confidence: 99%
“…Yamauchi et al reported that the bone-implant contact (BIC) ratio for both Ti and Ti6Al4V UV-treated implants significantly increased at 2 weeks [ 3 ]. UV irradiation was also found to have an antimicrobial effect in the early stage after implantation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The light source mounted in the UVI device is a low-pressure mercury lamp, which emits UV light predominantly at 254 and 185 nm. Under these conditions, each Ti surface received approximately 8-10 mW/cm 2 of radiation 11) . UV5 corresponded to a dose of 3 J/cm 2 .…”
Section: Surface Treatmentmentioning
confidence: 99%